Meditate with me : a step-by-step mindfulness journey - Gates, Mariam (Dial Books for Young Readers, 2017)
"This accessible and fun guide to meditation and mindfulness is the perfect introduction for young children Meditation does a body good, and can even help kids as young as four or five. This practical guide is gentle, clear, and a pleasure to use. Kids will learn how to focus on their breath, on the sensations in their body, and on the sounds around them to help them relax, settle their busy minds, and understand their emotions. Illustrated with cheerful drawings of five animal friends, the book offers step-by-step directions and a repeating refrain: "Breathe in, and fill your whole body. Breathe out, and relax your whole body." It's an invigorating first experience of mindfulness that can be shared by parents and children at home, or by teachers and students in the classroom"--